MetAP-like Ebp1 occupies the human ribosomal tunnel exit and recruits flexible rRNA expansion segments - Wild, Klemens; Aleksić, Milan; Lapouge, Karine; Juaire, Keven D.; Flemming, Dirk; Pfeffer, Stefan; Sinning, Irmgard (Nature Communications, 2020)
The ErbB3 receptor binding protein Ebp1 binds to ribosomes and is linked to translational control. Here, the authors present the cryo-EM structure of human Ebp1 bound to a non-translating 80S ribosome and find that Ebp1 blocks the tunnel exit and recruits the rRNA expansion segment ES27L to the tunnel exit.